Pengaruh Konten Viral Terhadap Fomo Generasi Z Dalam Konsumsi Fashion Di Tiktok - Adeliana Putri, Adhinda; Deri Apriadi (Pusat Riset dan Inovasi Nasional, 2025)
The study focuses on how viral content on TikTok influences the Fear of Missing Out (FOMO) experience among Generation Z, particularly in the context of fashion product consumption behavior. This topic is important because Generation Z, as active social media users, are vulnerable to digital social pressure influenced by viral content. The research method used an online survey involving 38 Gen Z TikTok users, with data analyzed using simple linear regression via SPSS. The results indicate a positive and significant effect of viral content on FOMO, with a contribution of 53.7% (R² = 0.537). These findings affirm the role of social media in shaping consumer behavior based on digital trends. The implications are important for the fashion industry and digital marketing in designing effective promotional strategies while considering ethics and digital literacy. In conclusion, viral content on TikTok significantly contributes to increasing FOMO among Generation Z, highlighting the need to enhance digital education to help young consumers manage the influence of online trends.